Entrepreneurial ecosystems: a systematic review. Issue 4 (3rd September 2018) - Maroufkhani, Parisa; Wagner, Ralf; Wan Ismail, Wan Khairuzzaman
Abstract : Purpose: The literature on entrepreneurial ecosystems is fragmented, and yet, no studies have paid attention to integrating the available studies. The purpose of this study is to provide a systematic review of contributions related to entrepreneurial ecosystems. Design/methodology/approach: This literature review evaluates studies that are covered in the Web of Science index. Findings: In addition to the recent state of research (covering industries, geographical scopes, methodologies, etc.), this study provides an extension of Isenberg's (2011) model of entrepreneurial ecosystems. Research limitations/implications: A new avenue arises for both conceptual and empirical research by emphasizing crowdsourcing as a contributing element for the entrepreneurial ecosystem. Future studies can evaluate the effectiveness of different types of crowdsourcing profoundly to make sure whether creating a promising ecosystem all types of crowdsourcing have a similar value or impact. Practical implications: For public policy and local decision-makers, both collaboration opportunities and interaction interfaces between the stakeholders of the entrepreneurial need to be reconsidered in the design of entrepreneurial ecosystems. Social implications: Higher degrees of collaboration, information exchange and innovation are likely to yield favorable entrepreneurship environments. Originality/value: Novelty of this study arises from integrating crowdsourcing theory in the systematic review of entrepreneurial ecosystems.